2021
DOI: 10.3390/ani11030840
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity and Community Variation in the Intestines of Layer Chickens

Abstract: The intestinal microbiota is increasingly recognized as an important component of host health, metabolism and immunity. Early gut colonizers are pivotal in the establishment of microbial community structures affecting the health and growth performance of chickens. White Lohmann layer is a common commercial breed. Therefore, this breed was selected to study the pattern of changes of microbiota with age. In this study, the duodenum, caecum and colorectum contents of white Lohmann layer chickens from same environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 64 publications
5
36
1
1
Order By: Relevance
“…In addition, we found that while Bacteroides , Prevotella , Faecalibacterium , and Ruminococcus were the predominant genera in ceca, their presence was rarer in other intestinal segments. Similar findings were reported in studies performed in commercial broilers ( 17 ) and layers ( 18 , 20 ). Bacteroides spp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, we found that while Bacteroides , Prevotella , Faecalibacterium , and Ruminococcus were the predominant genera in ceca, their presence was rarer in other intestinal segments. Similar findings were reported in studies performed in commercial broilers ( 17 ) and layers ( 18 , 20 ). Bacteroides spp.…”
Section: Discussionsupporting
confidence: 91%
“…The microbiota in the gastrointestinal tract have an important function in improving food absorption and boosting the immune system, thus influencing both host development and health ( 15 , 16 ). Recent studies reported that the chicken microbiome varies in different intestinal segments ( 17 20 ). The most densely inhabited microbial community within the chicken intestine was observed in the ceca, a pair of blind-ended sacs that open at the junction between the small and large intestine ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high SE colonization result is likely due to the immaturity of the intestinal microbiota and immune system in 8-day-old chicks. The is less microbial diversity in younger chickens compared with older chicken ( Cui et al., 2017 ) and diversity of bacterial species in cecal contents of layer chicks drastically increased between d 0 to 24 ( Xiao et al., 2021 ). In this trial, significant increase of bacterial species diversity was only confirmed in DY at 14 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining egg shell thickness requires adequate levels of calcium in the feed, and the ability to take up the calcium. It has been suggested that the microbiota composition also may promote the intestinal absorption of calcium and support competitive exclusion of harmful bacteria [ 38 ]. Thus, it seems a likely assumption that the BS-Hi hens, which were able to maintain a high breaking strength at an age of 92 weeks, were better equipped to absorb calcium from the feed in the gut than the BS-Lo hens.…”
Section: Discussionmentioning
confidence: 99%